2020
DOI: 10.3389/fgene.2020.00953
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Clinical Characteristics of Patients With Hereditary Spherocytosis in Hubei Province of China

Abstract: Hereditary spherocytosis (HS) is an inherited disorder characterized by anemia, splenomegaly, and spherical-shaped erythrocytes, caused by mutations in erythrocyte membrane Protein Genes ( ANK1 , SPTB , SLC4A1 , SPTA1 , and EPB42 ). We investigated molecular spectrum and genotype-phenotype correlation in HS patients in Hubei province, central China. Twenty-three patients with HS were included. A n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 30 publications
4
29
2
Order By: Relevance
“…The study of Michaels et al showed that the MCHC of most HS cases was > 359 g/L ( Michaels et al, 1997 ). However, in our study, we found that 100% of patients had MCHC < 359 g/L, similar to the study of Wang ( Wang et al, 2020 ). In their report, it was found that 89% of patients (17/19) had MCHC < 35.9 g/dL, which further confirmed that MCHC has a poor measurement effect on HS.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The study of Michaels et al showed that the MCHC of most HS cases was > 359 g/L ( Michaels et al, 1997 ). However, in our study, we found that 100% of patients had MCHC < 359 g/L, similar to the study of Wang ( Wang et al, 2020 ). In their report, it was found that 89% of patients (17/19) had MCHC < 35.9 g/dL, which further confirmed that MCHC has a poor measurement effect on HS.…”
Section: Discussionsupporting
confidence: 92%
“…Hb, RBC, and HCT of all patients without splenectomy were decreased. MCH and MCHC levels were within the normal range, which was similar to the recent studies in India and Hubei ( Aggarwal et al, 2020 ; Wang et al, 2020 ). The study of Michaels et al showed that the MCHC of most HS cases was > 359 g/L ( Michaels et al, 1997 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations